Karakteristik Islam dalam Tata Kelola Lingkungan Hidup: Studi Kasus Pemberian IUP Pertambangan dan Mineral kepada Organisasi Masyarakat Keagamaan - Hening Purwati Parlan; Saiful Bahri (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The article examines Islamic characteristics of environmental governance with a focus on the granting of mining and mineral business licences (IUPs) to religious organisations. This case study was conducted to understand how Islamic principles can be applied in sustainable and responsible environmental governance practices. The article used a qualitative approach with a case study method involving document analysis and participatory observation. The results showed that Islamic principles, such as tawhid (the oneness of God), Khilafah (human leadership on earth), and Kaslahah (public interest), play an important role in decision-making regarding the granting of IUPs. In addition, this study found that the application of Islamic values in environmental governance can improve compliance with environmental regulations and strengthen commitment to nature conservation. These findings make an important contribution to the development of policies that integrate religious values in environmental governance in Indonesia.